'English Is Always Proportional to One's Wealth': English, English Language Education, and Social Reproduction in South Korea - Choi, Lee Jin (Multilingua, 2021)
While quality English language education is not equally accessible in many EFL countries, neoliberalism and its ideology of language as a neutral skill that everyone can acquire has obscured inequalities caused by the heavy emphasis on English as a dominant world language. Using South Korea as an example, I examine how individuals, especially young adults, living in the neoliberal market economy perceive and recognize the overwhelming emphasis on English as a dominant world language and its underlying mechanisms that contribute to social reproduction in EFL countries. In analyzing the popular Korean discourse Theory of Spoon Class (sujeogyegeublon), I examine how English is beginning to be recognized as an active tool to maintain and solidify social class reproduction, and how the construction of English as a purchasable good then results in feelings of despair, hopelessness and resentment among individuals, especially young adults who need to survive in the precarious job market with rising unemployment rates and prolonged economic stagnation.